Surgical treatment of systemic embolization by cardiac metastasis of lung cancer. (November 2014) - Santise, Gianluca; Raffa, Giuseppe Maria; Pilato, Michele
Pulmonary vein infiltration from a malignant lung neoplasm is a serious condition that may result in a constant source of systemic emboli. Although surgery is often indicated to prevent recurrent embolism, aggressive approaches have shown a high rate of perioperative morbidity. We herein report the case of a patient diagnosed with lung cancer infiltrating the cardiac chambers through the left superior pulmonary vein, who was treated by left pulmonary vein patch closure as a preventive and less invasive measure to reduce the thromboembolic risk.